Preparation and Absorption Carbon Monoxide Properties of a Novel Flame Retardants Based Fire-Fighting Foam - Li, Xiujuan; Guo, Ruisong; Qian, Xiaodong (Frontiers in Materials, 2021)
The toxicity of CO threatens the life of people in the fire site. In this study, smoke-suppressed fire extinguishing agent is prepared by adding flame retardant into the AFFF water film foam extinguishing agent. The new extinguishing agent shows a good performance of absorption of CO and reducing the flue gas temperature. The concentration of CO is decreased below 131 ppm and flue gas temperature is basically kept below 40℃, which is 367 ppm and 83.1℃ less than that in free-fire. Using new extinguishing agent can effectively reduce the harm to the trapped personnel and firemen in the fire site. It is of great significance. The harm of CO concentration below 131ppm and flue gas temperature below 40℃ is low. The time to reach the maximum CO concentration and the maximum flue gas temperature is delayed, which ensures that people have more time to escape. Even if there is not enough time to escape, people will not be seriously threatened.